COVID-19 AND THE CRY OF THE POOR: Sensitivity and Solidarity - Nandhikkara, Jose (Journal of Dharma, 2020)
COVID-19 is an infectious respiratory disease caused by the coronavirus, SARS-CoV-2, first reported in Wuhan, China, in December 2019. Since then as I write this on 10 June 2020, it spread globally to 188 countries with 7,127,753 confirmed cases and 407,159 deaths. The new coronavirus simply took over the planet and devastated the world, said Anthony Fauci, the head of US COVID-19 task force: “We’ve never been in a situation like that ever in history, where we had to essentially shut down the planet.” Together with physical health, the pandemic affects mental health: Fear and worry of contamination can leave one stressed, anxious, and powerless, draining the weak and vulnerable emotionally leading to depression and even suicide. The response to the COVID-19 pandemic raises many ethical issues, related to priority-setting, health-care workers’ rights and obligations, clinical trials, social distancing, surveillance, etc. Principles and values such as cost-effectiveness, transparency, stewardship, autonomy, beneficence, fairness, justice, and many others inform policy making for institutions and Governments.